2020
DOI: 10.3389/fnmol.2020.617422
|View full text |Cite
|
Sign up to set email alerts
|

Target Molecules of STIM Proteins in the Central Nervous System

Abstract: Stromal interaction molecules (STIMs), including STIM1 and STIM2, are single-pass transmembrane proteins that are located predominantly in the endoplasmic reticulum (ER). They serve as calcium ion (Ca2+) sensors within the ER. In the central nervous system (CNS), they are involved mainly in Orai-mediated store-operated Ca2+ entry (SOCE). The key molecular components of the SOCE pathway are well-characterized, but the molecular mechanisms that underlie the regulation of this pathway need further investigation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 231 publications
(411 reference statements)
0
30
0
Order By: Relevance
“…The SOCE process, whereby calcium influx across the plasma membrane, is related to the IP3 receptor (IP3R) leading to its activation in response to depletion of intracellular calcium stores of the endoplasmic reticulum (ER) [55]. Our results showed that the blocking of FPRL by AaTs-1 reduced SOCE by acting both on SOC (store operated channels), an effect observed near IC 50 for AaTs-1, and for higher AaTs-1 concentrations on ER release and most likely on the stromal interaction molecules STIMs (the reticular protein partners connected to SOC) [56]. Both concentrations SOCE were reduced, which could explain the AaTs-1 effect on cell proliferation.…”
Section: Discussionmentioning
confidence: 69%
“…The SOCE process, whereby calcium influx across the plasma membrane, is related to the IP3 receptor (IP3R) leading to its activation in response to depletion of intracellular calcium stores of the endoplasmic reticulum (ER) [55]. Our results showed that the blocking of FPRL by AaTs-1 reduced SOCE by acting both on SOC (store operated channels), an effect observed near IC 50 for AaTs-1, and for higher AaTs-1 concentrations on ER release and most likely on the stromal interaction molecules STIMs (the reticular protein partners connected to SOC) [56]. Both concentrations SOCE were reduced, which could explain the AaTs-1 effect on cell proliferation.…”
Section: Discussionmentioning
confidence: 69%
“…The lowered cytosolic Ca 2+ fluxes in Rtnl1 mutants (Fig. 5) might potentially be explained by disruption of ER-PM contacts that contain STIM (Serwach & Gruszczynska-Biegala, 2020). However, the lack of any decrease in resting Ca 2+ levels in any compartment in Rtnl1 mutants does not provide any evidence for a defect in SOCE.…”
Section: Discussionmentioning
confidence: 90%
“…ER calcium sensor STIM1 senses the drop in calcium concentration and relocalizes to ER–PM contacts, where it activates PM-localized calcium channel Orai1 to allow the entry of extracellular calcium. Sarco/ER calcium transport ATPase (SERCA) pumps then take up the calcium into the ER ( Serwach and Gruszczynska-biegala, 2020 ).…”
Section: Functional Studies Of Mammalian Jph1 and Jph2 In Musclesmentioning
confidence: 99%